Changes in Tax Revenue in Comparison with GDP at Current Prices in Syria (a 2000-to-2016 Study) - Zedan, Rami Ali (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Tax revenue is one of the most important ways for countries to supplement their public budgets with revenues needed for public spending. Given its characteristics and qualities, tax revenue is a very important tool of widespread fiscal policies used by countries to reduce the problems experienced by their economies, such as inflation, stagnation and unemployment. Tax changes are supposed to be in line with GDP changes, in the rise and fall. In this research I will examine the change in tax revenues in Syria compared to the change in GDP at current prices in the period from 2000 to 2016. The conclusion the study reaches is that the changes in taxes are incompatible with the changes in the GDP. This shows the inflexibility of the taxation system in Syria, which in turn has led to low tax revenues and a decrease in tax burden. تعتبر الإيرادات الضريبية إحدى أهم الطرق التي تلجأ إليها الدول لرفد موازناتها العامة بالإيرادات اللازمة للإنفاق العام، وذلك بالنظر للخصائص والسمات التي تتمتع بها، والتي تجعلها أداةً بالغة الأهمية من أدوات السياسة المالية المعروفة، التي تستخدمها الدول للحد من مشكلات تمر بها اقتصادياتها، كالتضخم والركود والبطالة ... هذا ويُفتَرَض أن تتماشى تغيرات الضرائب مع تغيرات الناتج المحلي الإجمالي، سواء بالصعود أو الهبوط. في بحثنا هذا سوف ندرس تغير الإيرادات الضريبية في سورية، مقارنةً بتغير الناتج المحلي الإجمالي بالأسعار الجارية منذ عام 2000 حتى عام 2016، حيث سيتبين لنا من خلال الدراسة عدم مواكبة تغيرات الضرائب للتغيرات الحاصلة في الناتج، وهو ما يعني عدم مرونة النظام الضريبي في سورية، والذي أدى بدوره إلى ضعف حصيلة الإيرادات الضريبية، وانخفاض العبء الضريبي.